JENIS DAN SEBARAN SATWA BURUNG DI PULAU NUSA MANU DAN NUSA LEUN NEGERI SAWAI KECAMATAN SERAM UTARA, MALUKU TENGAH - Tjio, Andika; Badaruddin, Ernywati; Kaya, Manuel (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
This research aims to determine (1) the types of bird species on Nusa Manu and Nusa Leun Islands, Sawai Village (2) The distribution of bird species on Nusa Manu and Nusa Leun Islands, Sawai Village. This research uses the census method to collect data on bird species. The research results show that there are 13 species of birds on Nusa Manu Island and 12 species of birds on Niusa Leun Island. The highest distribution of bird species on the island of Nusa Manu is black honey (Nectariana aspasia), sriganti honey (Nectariana jugularis), Seram honey (Lichmera monticola) and garden fan (Rhipidura leucophrys) with a frequency of 11.43%, while the lowest distribution of bird species is , sea croak (Butorides striatus) and coral egret (Egretta sacra) with a frequency of 2.86%. The highest bird distribution on Nusa Leun Island is black honey (Nectariana aspasia) and garden fan (Rhipidura leucophrys) with a frequency of 14.29%, while the lowest bird distribution is sea cockerel (Butorides striatus), great egret (Egretta alba). and eastern elephant (Numenius madagascariensis) with a frequency of 3.5-7%.